2009
DOI: 10.1016/j.jcin.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Outcomes With Sirolimus-Eluting Stents in Total Coronary Occlusions

Abstract: Despite greater lesion complexity than prior TCO trials, percutaneous revascularization with SES appears safe and results in substantial reductions in angiographic restenosis and failed patency and a low rate of repeat revascularization. These findings support the use of SES in TCO revascularization. (The ACROSS/TOSCA Trial; NCT00378612).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…6,[8][9][10]21 In the present study, ostial stent location and lesions with hinge motion, tortuosity, or calcification were independent predictors of SF after EES implantation. Among these, hinge motion and tortuosity contributed most greatly to the incidence of SF.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…6,[8][9][10]21 In the present study, ostial stent location and lesions with hinge motion, tortuosity, or calcification were independent predictors of SF after EES implantation. Among these, hinge motion and tortuosity contributed most greatly to the incidence of SF.…”
Section: Discussionsupporting
confidence: 50%
“…3,4 Stent fracture (SF) after DES implantation has recently become an important concern because of its potential association with ISR, TLR, and ST. 5 SF after sirolimus-eluting stent (SES) implantation has been reported to be associated with an increased risk of ISR, ranging from 15% to 60%, and with higher cardiac event rates within a 1-year observation period. [6][7][8][9][10][11] A recently published pathological study of 144 autopsy cases with DES implantation detected SF in 29% of lesions, and SFs with gaps within the stent body were associated with histological events, such as ST or restenosis, in 67% of cases. 12 The everolimus-eluting stent (EES) is a new-generation DES, based on a thin-strut, cobalt-chromium alloy platform and releases everolimus, a semisynthetic sirolimus analog, from an acrylic and fluoropolymer mixture.…”
mentioning
confidence: 99%
“…15 In the current era, however, a 1.9% to 16.0% incidence of SF after SES implantation has been recognized as one of the clinically relevant contributors to focal in-stent restenosis. [5][6][7][8][9][10][11][12] In the current study, SF patients had a significantly higher rate of in-stent restenosis at 6 to 9 months, as compared with non-SF patients. An increase in mechanical stimulation of the vessel wall, the loss of mechanical scaffolding of the stent, and a decrease in local drug delivery may have predominantly contributed to the higher rates of in-stent restenosis.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, the presence of stent fracture (SF) after SES implantation has been reported to be associated with an increased risk of in-stent restenosis, ranging from 15% to 60%, [5][6][7][8][9][10][11][12] with higher cardiac event rates within a 1-year observation period. [5][6][7][8]10,12 A recently published pathological study in 144 autopsy cases of patients who had received drug-eluting stents (DES) demonstrated that SF was detected in 29% of lesions, and the presence of SF with gap within the stent body was associated with a histological event, such as stent thrombosis or restenosis, in 67% of cases. 13 Because the duration and severity of arterial responses at the site of SF, which may have an adverse effect on outcomes, as well as the time point at which the SF occurs after SES implantation remain uncertain, the clinical impact of SF on long-term outcomes should be evaluated.…”
mentioning
confidence: 99%
“…Successful recanalization of CTO in patients with viable myocardium may decrease the need for bypass surgery, reduce angina symptoms and improve long-term survival [1][2][3][4]. PCI instruments and the techniques for CTO lesions had improved over time [5], and excellent outcomes have been achieved in multiple pilot studies, especially with the combined use of drug-eluting stents [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%